S-28-8: THE ASCOT LEGACY COHORT: THE LONG-TERM EFFECTS OF BLOOD PRESSURE AND BLOOD PRESSURE VARIABILITY ON CARDIOVASCULAR AND RENAL OUTCOMES. (January 2023) - Sever, Peter; Gupta, Ajay; Whiteley, William; Godec, Thomas; Rostamian, Somayeh; Mackay, Judith; Poulter, Neil; Whitehouse, Andrew
Abstract : Introduction: We have previously shown that visit to visit systolic blood pressure variability (BPV) was the major predictor of cardiovascular outcomes in ASCOT, a trial in hypertensive participants randomised to amlodipine based or atenolol based treatment. Treatment differences in BPV accounted for the benefits of the amlodipine based regimen over the atenolol based regimen on cardiovascular (CV) events during the trial. We now report observations from the 20 yr follow up of UK participants to determine the long term impact of mean systolic blood pressure control during the trial and BPV on CV and renal outcomes. Methods: In the ASCOT Legacy Cohort, 7, 092 hypertensive participants with hypertension, aged 40 to 79 years, with at least three other CV risk factors have been followed for up to 20 years. All available SBP visit records (n = 100, 933) were included after excluding the first six months observations. The mean of SBP as a measure of BP control and the standard deviation (SD) of all SBPs as an estimate of visit to visit BPV were calculated for the five years of the trial. Participants were then followed for up to 15 years after the end of the trial using the UK National Health Service (NHS) electronic health records. CV and renal outcomes were measured using Cox proportional hazards model adjusted for confounding variables. Results: Although in trial mean SBP predicted long term CV and renal outcomes, SBP variability independent of mean SBP was a strong predictor of both CV and renal outcomes. (Table) Those originally assigned amlodipine based (vs. atenolol based) treatment had a significantly reduced long term risk of risk of stroke [0.82, 0.72 to 0.93, p = 0.003], total CV events and procedures [0.93, 0.88 to 0.98, p = 0.008], total coronary events [0.92, 0.86 to 0.99, p = 0.024] and atrial fibrillation [0.91, 95% CI, 0.83 to 0.99, p = 0.030]. There was no significant difference in the incidence of heart failure, non fatal myocardial infarction and fatal CHD or renal events. Conclusions: Amlodipine based treatment conferred long term advantages over atenolol based treatment on several CV outcomes. Both mean SBP and BPV are strong predictors of long term CV and renal outcomes, but BPV, independent of mean BP, confers a significant additional risk and should be considered for future preventive and therapeutic strategies.